2010
DOI: 10.5194/angeo-28-2015-2010
|View full text |Cite
|
Sign up to set email alerts
|

Polar cap flow channel events: spontaneous and driven responses

Abstract: Abstract. We present two case studies of specific flow channel events appearing at the dusk and/or dawn polar cap boundary during passage at Earth of interplanetary (IP) coronal mass ejections (ICMEs) on 10 January and 25 July 2004. The channels of enhanced (>1 km/s) antisunward convection are documented by SuperDARN radars and dawn-dusk crossings of the polar cap by the DMSP F13 satellite. The relationship with Birkeland currents (C1-C2) located poleward of the traditional R1-R2 currents is demonstrated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 26 publications
2
31
2
Order By: Relevance
“…The unusually strong enhancement of SAPS at an earlier time (1100–1200 UT; see shaded interval in grey in Figure c) was investigated by Makarevich et al [] suggesting the important role of convection bursts in SAPS intensification. Convection bursts occur during FTEs [ Southwood , ; Lee , ] when reconnection rates become enhanced briefly and intensively [ Russell and Elphic , ] and leave their signatures in convection flows appearing as various types of FCs [ Sandholt and Farrugia , ; Sandholt et al ., , ]. Adding to the study of Makarevich et al [], we show that during their earlier and our later SAPS detection, the LANL plots tracked the signatures of substorm injections.…”
Section: Discussionsupporting
confidence: 78%
“…The unusually strong enhancement of SAPS at an earlier time (1100–1200 UT; see shaded interval in grey in Figure c) was investigated by Makarevich et al [] suggesting the important role of convection bursts in SAPS intensification. Convection bursts occur during FTEs [ Southwood , ; Lee , ] when reconnection rates become enhanced briefly and intensively [ Russell and Elphic , ] and leave their signatures in convection flows appearing as various types of FCs [ Sandholt and Farrugia , ; Sandholt et al ., , ]. Adding to the study of Makarevich et al [], we show that during their earlier and our later SAPS detection, the LANL plots tracked the signatures of substorm injections.…”
Section: Discussionsupporting
confidence: 78%
“…The excitation of FC 1-FC 2 flows (see Fig. 2) during the interval 14:50-15:00 UT on this day can be seen in the IMAGE magnetometer data reported by Sandholt et al (2010) (see their Fig. 3).…”
Section: Pre-substorm Conditionsmentioning
confidence: 52%
“…FC 2 is a result of the persistence of open flux tubes previously opened by bursts of reconnection (flux transfer events; FTEs) along the flanks of the polar cap, as predicted by Southwood (1987). The presence of these flows has been documented by Sandholt et al (2010). The IMF B y dependence and the role of conductivity gradients at the polar cap boundary for the formation of these flow channels have been discussed by Sandholt and Farrugia (2009).…”
Section: Observation Geometry and Global Convection Contextmentioning
confidence: 93%
See 1 more Smart Citation
“…The diagrams illustrate the various flow channel (FC) types in magnetic local time and magnetic latitude coordinates. Modified after Figure 1 of Sandholt et al (), these FCs are shown in the context of the Dungey polar convection operating in a (a) forward or (b) reversed manner. Modified after Figure 3 of Sandholt et al (), the diagrams illustrate the various FCs under IMF B Z < 0 conditions for (c) B Y < 0 and (d) B Y > 0 orientations.…”
Section: Introductionmentioning
confidence: 99%